Relationship between Plasma Neuregulin-1 and MDA Levels with Severity of CAD - Aliska, Gestina; Fadil, Muhammad; Ilhami, Yose Ramda; Usman, Elly; Raditya, Ivan Mahendra; Zhuhra, Rahma Tsania; Alfadli, Robby (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Neuregulins (NRGs) are one of the epidermal growth factors (EGF) superfamily, which released in cellular injuries, such as neurons and myocardial cells. Neuregulin-1β (NRG-1β) could be activated when stress happens to myocardial cells, acting as a survival factor to repair the injury. Malondialdehyde (MDA) is also produced during oxidative stress in cardiac injury. In vivo study of myocardial cells in rats and dogs that got ischemic, dilated, and viral cardiomyopathy showed that NRG-1 could improve the injured cardiac performance, attenuated pathological changes, and prolonged survival of the cells. AIM: We aimed to observe NRG-1 levels in CAD patients in Indonesia, mainly focused in Minang ethnicity. This study also analyzes the relationship between NRG-1 and MDA with CAD’s severity. METHODS: We measured plasma NRG-1 in 61 nondiabetic patients within 38–82 years old range with STEMI, NSTEMI, and UAP. RESULTS: We found their plasma NRG1, respectively, was 10.3 (1.9–38.2) ng/ml, 14.3 ± 7.2 ng/ml, and 7.05 (4.5–0.4) ng/mL. Plasma NRG 1 increased in AMI patients. CONCLUSION: This study concludes that NRG1’s activated during cardiac cells injury, in any AMI.